Effect of thermal ageing on the evolution of microstructure and degradation of hardness of 2.25Cr-1Mo steel - Jha B.B.; Mishra B.K.; Satpati B.; Ojha S.N. (My University, 2025)
Thermal ageing of various durations and at various temperatures was performed in order to understand microstructural changes associated with precipitation and coarsening of carbides in 2.25Cr-1Mo steel. The severity of thermal ageing is expressed in terms of the Larson-Miller parameter (LMP). The microstructural examinations were carried out by optical and scanning electron microscopy techniques. A transmission electron microscope (TEM) and an electron probe micro analyzer (EPMA) were used to identify the carbide particles, and to analyse the shape, size and distribution of the precipitate phases. Influence of these precipitates on hardness degradation of the steel has been examined. The reasons for the variation in the microstructure and for the hardness degradation of steel arising from thermal ageing are discussed.